Management of chronic lateral instability due to lateral collateral ligament deficiency after total knee arthroplasty: A case report - Aasis Unnanuntana (2018)
Introduction. Lateral instability following total knee arthroplasty (TKA) is a rare condition with limited report of treatment options. The objective of this case presentation is to demonstrate the outcomes of different surgical procedures performed in a single patient with lateral collateral ligament (LCL) deficiency. Case presentation. We present a case of chronic lateral instability due to LCL deficiency after primary TKA in a 47-year-old Caucasian woman with an obesity problem. Multiple treatment options have been performed in order to manage this problem, including the following: ligament reconstruction; combined ligament reconstruction and constrained implant; and rotating-hinge knee prosthesis that was the most recent surgery. All ligament reconstruction procedures failed within one year. The varus-valgus constrained prosthesis provided stability for six years. Conclusions. Ligament reconstruction alone cannot provide enough stability for the treatment of chronic lateral instability in patients with obesity problems and LCL deficiency. When the reconstruction fails, a salvage procedure with rotating-hinge knee is still available. © 2010 Unnanuntana et al; licensee BioMed Central Ltd.